Bondage : Labor and Rights in Eurasia from the Sixteenth to the Early Twentieth Centuries - Stanziani, Alessandro (Berghahn Books)
For the first time, this book provides the global history of labor in Central Eurasia, Russia, Europe, and the Indian Ocean between the 16th and 20th centuries. It contests common views on free and unfree labor, comparing the latter to many Western countries where wage conditions resembled those of domestic servants. This gave rise to extreme forms of dependency in the colonies, not only under slavery, but also afterwards via indentured labor in the Indian Ocean and obligatory labor in Africa. Stanziani shows that unfree labor and forms of economic coercion were perfectly compatible with market development and capitalism, proven by the consistent economic growth that took place all over Eurasia between the 17th and the 19th centuries. This growth was labor intensive: commercial expansion, transformations in agriculture, and the first industrial revolution required more labor, not less.
English
Keywords: General & world history; History; global labor history; indentured servitude; slavery; abolition; workers' rights; Eurasia; Peasant; Russia; Serfdom